Review of the use of pretest probability for molecular testing in non-small cell lung cancer and overview of new mutations that may affect clinical practice. (June 2017) - Martin, Petra; Leighl, Natasha B.
This article considers the use of pretest probability in non-small cell lung cancer (NSCLC) and how its use in EGFR testing has helped establish clinical guidelines on selecting patients for EGFR testing. With an ever-increasing number of molecular abnormalities being identified and often limited tissue available for testing, the use of pretest probability will need to be increasingly considered in the future for selecting investigations and treatments in patients. In addition we review new mutations that have the potential to affect clinical practice.